STUDI ETNOGRAFI KOMUNIKASI TERKAIT PRAKTIK KOMUNIKASI BUDAYA DAN PELESTARIAN IDENTITAS ETNIK KOMUNITAS ADAT BERCO DI DESA LEBANGKAR KABUPATEN SUMBAWA - Iranda Yudhatama; Widyaningtyas Virgo Kartika; Halla Sayyidah Muflichah (AKADEMI KOMUNIKASI RADYA BINATAMA, 2026)
This study aims to analyze the cultural communication practices of the Berco indigenous people in Lebangkar Village, Ropang District, Sumbawa Regency, and their role in preserving ethnic identity amidst social change and modernization. The Berco indigenous people possess unique cultural characteristics, particularly related to the use of the Berco language, their customary value system, and various traditional rituals passed down through generations. This study employed a qualitative approach with rapid ethnography to gain an in-depth understanding of cultural communication patterns in a relatively short period of time. Data collection was conducted through participant observation, in-depth interviews with traditional leaders, and community members. Data analysis employed the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data presentation, and conclusion drawing. The results indicate that cultural communication among the Berco people occurs through three main domains: ritual communication, linguistic communication, and customary institutional communication. The Berco language serves as a symbol of ethnic identity and a medium for transmitting cultural values. The practice of rapulung (customary deliberation) serves as the primary means of reproducing social norms and collective decision-making. Furthermore, traditional rituals and ancestral sites serve as symbolic communication media that strengthen group solidarity. This research finds that the preservation of Berco ethnic identity depends on the continuity of intergenerational communication, the strengthening of customary institutions, and cultural adaptation to developments in communication technology. These findings enrich the ethnographic study of communication among indigenous peoples in Indonesia, particularly in the context of preserving local cultural identity.